2022
DOI: 10.1111/jcpe.13748
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture regulates macrophage, neutrophil, and oral microbiota to alleviate alveolar bone loss and inflammation in experimental ligature‐induced periodontitis

Abstract: Aim Electroacupuncture (EA) regulates distant body physiology through somatic sensory autonomic reflexes, balances the microbiome, and can promote the release of immune cells into bloodstream, thereby inhibiting severe systemic inflammation. This makes it possible to use EA as an integrated treatment for periodontitis. Materials and Methods In this study, EA was applied to the ST36 acupoints in a ligature‐induced periodontitis (LIP) mouse model. Then the effects of EA on periodontal myeloid cells, cytokines, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Periodontitis causes alveolar bone destruction in the gingival tissue along with extensive macrophage infiltration ( Liu et al, 2023 ). Macrophages are both heterogeneous and plastic, have polarized phenotypes and exhibit different functions depending on their environment ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis causes alveolar bone destruction in the gingival tissue along with extensive macrophage infiltration ( Liu et al, 2023 ). Macrophages are both heterogeneous and plastic, have polarized phenotypes and exhibit different functions depending on their environment ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CTR and LIP groups were given equivalent volumes of olive oil. For LIP, mice were anaesthetized with inhaled isoflurane and a 5-0 ligature wire was subsequently placed around the bilateral maxillary second molars (K. Liu et al, 2023;Wu et al, 2023).…”
Section: Network Pharmacologymentioning
confidence: 99%
“…Our previous findings showed that neutrophils are key immune cells involved in the development of periodontitis and may play a critical role in host defence against infection (K. Liu et al, 2023). However, pharmacological manipulation or regulation is difficult in terms of neutrophils, which have a short survival period, rapidly undergo apoptosis or release extracellular neutrophil traps (NETs) consisting of reticulocyte DNA and antimicrobial proteins upon stimulation by pathogens or oxidative stress (Singhal & Kumar, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, in acute infections and in patients with systemic diseases, conventional nonsurgical or surgical therapy alone may not provide satisfactory therapeutic results, thus a complementary treatment is urgently required, such as the electroacupuncture and the application of different agents (melatonin, hypochlorite, or chlorhexidine, etc. ), which have different results in terms of the clinical attachment level and anti-inflammatory effect [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%